Fungitoxity and chemical composition of rosemary essential oil (Rosmarinus officinalis) on Aspergillus flavus (Research, Society and Development, 2020)
Fungi are among the main responsible for damage and loss in various foods. They have the ability to produce secondary metabolites when subjected to ideal conditions, known as mycotoxins, highly toxic substances that can contaminate products intended for both human and animal food causing damage to health. The control of these fungi has been done through synthetic substances, which are harmful to man and the environment. Thus, it is necessary to search for alternative methods of controlling these microorganisms. In this context, essential oils are a possible option. The objective of this study was to identify the main components and evaluate the effectiveness of the essential oil of rosemary (Rosmarinus officinalis) for controlling the fungus Aspergillus flavus. Initially, the effect of essential oils on mycelial growth of the fungus was verified in in vitro tests at doses of: 0.8; 1.6; 3.2; 6.4; 12.8; 15; 17.5; 20; 22.5 and 25 µL/mL, this being the dose with the greatest fungal control. Based on the results of the in vitro tests, serial microdilution was performed in microplates to find the minimum inhibitory concentration, which was 25 µL/mL. The results showed that the essential oil showed fungicidal potential on A. flavus. The main components of the essential oil, identified by gas chromatography, in order of concentration, were: 1,8-cineol, camphor and β-pinene.